Pengaruh Locus of Control (Lokus Kendali), Self Efficacy (Efikasi Diri) dan Lingkungan Kerja terhadap Kinerja Karyawan pada Bank Sumut Syariah KCP Karya - Aprilliyansyah, Ary Bagas; Nasution, Muhammad Lathief Ilhamy (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of Locus of Control, Self-Efficacy, and Work Environment on Employee Performance at Bank Sumut Syariah KCP Karya. The background of this research is based on the phenomenon of declining employee performance in several branches, including KCP Karya, which is suspected to be influenced by psychological factors and workplace conditions. The study employed a quantitative approach using a survey method, distributing questionnaires to all employees (22 respondents), and analyzing the data with SPSS. The results show that, partially, all three independent variables—locus of control (p = 0.003), self-efficacy (p = 0.000), and work environment (p = 0.041)—have a significant effect on employee performance. Simultaneously, the three variables also significantly influence employee performance with a significance value of 0.000 (< 0.05) and an Adjusted R² of 81.9%, indicating a strong contribution of these variables to performance outcomes. The study concludes that improving internal locus of control, enhancing self-efficacy, and creating a conducive work environment significantly contribute to better employee performance. These findings have important implications for management in designing performance improvement strategies through psychological empowerment and workplace improvements. Keywords: Locus of Control, Self-Efficacy, Work Environment, Employee Performance, Islamic Bank